The Role and Significance of the Data Protection Officer in the Organization - Šidlauskas, Aurimas (Socialiniai tyrimai, 2021)
Following the entry into force of the General Data Protection Regulation (hereafter referred to as the GDPR), organizations that process personal data must ensure and demonstrate compliance with all of its principles. A new post, known as the Data Protection Officer (hereafter referred to as the DPO), has been created. The appointment of this official may be one of the measures necessary to implement the principle of accountability. The purpose of the article is to analyze the institute of the DPO as part of the regulatory framework laid down in the Regulation, and to provide generalized recommendations to organizations.
Keywords: General Data Protection Regulation (GDPR); Data Protection Officer (DPO); Personal data